2024
DOI: 10.26599/fshw.2022.9250063
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of kojic acid and tea polyphenols against Escherichia coli O157:H7 through transcriptomic analysis

Abstract: Escherichia coli O157:H7 is one of the major foodborne pathogenic bacterial that cause infectious diseases in humans. The previous found that a combination of kojic acid and tea polyphenols exhibited better activity against E. coli O157:H7 than using either alone. This study aimed to explore responses underlying the antibacterial mechanisms of kojic acid and tea polyphenols from the gene level. The functional enrichment analysis by comparing kojic acid and tea polyphenols individually or synergistically agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…With the development of high-throughput sequencing technologies, transcriptomic sequencing has played a significant role in studying the antimicrobial mechanisms of drugs [ 32 , 33 ]. Here, our transcriptional profiles revealed that the DEGs were primarily involved in bacterial energy metabolism, pyrimidine metabolism, DNA replication, and repair by comparing 5-FU treated groups with control group.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technologies, transcriptomic sequencing has played a significant role in studying the antimicrobial mechanisms of drugs [ 32 , 33 ]. Here, our transcriptional profiles revealed that the DEGs were primarily involved in bacterial energy metabolism, pyrimidine metabolism, DNA replication, and repair by comparing 5-FU treated groups with control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also strains that are opportunistic or highly pathogenic to humans when consumed through food (e.g., strains belonging to serotype O157:H7, etc.) [ 3 , 4 ]. S. aureus is widely found in the environment and secretes virulence factors that can easily contaminate meat, egg products and milk [ 5 ].…”
Section: Introductionmentioning
confidence: 99%